A implementação das sanções do Conselho de Segurança das Nações Unidas no Ordenamento Jurídico Brasileiro - Julia Soares Amaral (2018)
The work "The Implementation of the Sanctions of the United Nations Security Council in the Brazilian Legal Order" aims to analyze the state practice and the existing norms in Brazil, which allow the incorporation and compliance with certain international obligations. First, it is draw up the general picture of the Collective Security System to verify the nature of the obligation to be fulfilled and the current characteristics of the sanctions regimes. Then, it is studied how the domestic level of compliance is measured. From there, the internal procedures in comparative law and specific jurisprudence are studied, which points out weaknesses both in the internal and international order. The need for both orders to align and work together is proven and, for the verification of the Brazilian adequacy to the parameters established in one and the other, the case of Banco ABC is exposed. Furthermore, it is analyzed the Law 13.170 / 2015, which regulates the action of freezing of assets, rights or values, as a result from resolutions of the Security Council. The Financial Action Task Force against Money Laundering and the Financing of Terrorism - GAFI / FATF, its Recommendations and Evaluations from Brazil, are also valued, once it has a strong influence in the elaboration of such normative novation. Finally, the research shows that Brazilian initiatives are in line with movements observed in other countries, and also respond adequately to international and constitutional requirements. However, the correct application of the legislative novation presupposes the previous engagement of the CSONU in order to guarantee basic rights of individuals. In addition, some provisions of Law no. 13.170 / 2015 make room for misinterpretation and may lead to improprieties related to the model set by the UN Collective Security System. Thus, the considerations of the present work aim to point out adequate outputs to ensure the effectiveness of the Brazilian implementation of Security Council sanctions.